Examination of flow and heat transfer phenomena in ducts with dimples and protrusions (2020)
Dimples and protrusions create effective flow structure by improving fluid-surface interactions and fluid-mixing in ducts for thermal enhancement with minimal pressure losses. The experimental investigation of the effects of dimples and protrusions in the form of smooth surface duct, teardrop dimpled and teardrop protruded duct on flow and heat transfer characteristics were examined. Measurements of temperature, pressure drop and velocity were carried out in an experimental test rig and data collected were used to evaluate the heat transfer, flow friction, and the overall thermal performance of the three test ducts for the Reynolds number ranges from 30,000 to 57,000. The results show that with reference to the smooth duct, the Nusselt number of dimpled duct increases by 134.4% while those of protruded duct increases by 41.6%. Further, the heat transfer augmentation ranges from 1.53 to 4.76 and 1.07 to 2.32 for dimpled duct and protruded duct, respectively. In addition, the protruded duct demonstrated a higher friction factor in the range of 1.48 to 2.25 times that of the smooth duct, while dimpled duct friction factor increases in the range of 1.10 to 1.31. The overall result suggests that the dimpled duct have the best thermal-hydraulic performance as revealed by the performance evaluation criteria.